Three-tier inherent safety quantification (3-TISQ) for toxic release at preliminary design stage - Zaini, D. (Trans Tech Publications Ltd, 2014)
This paper proposes a new technique to evaluate the level of inherent safety of process plant during the preliminary design stage by using the combined assessment of process routes, streams and inherent risk for toxic release accidents. This technique is known as 3-Tier Inherent Safety Quantification (3-TISQ). The first tier is to screen the process routes and to select the âbestâ route that is inherently less hazardous. Next, the inherent safety level of the streams within the selected process route can be prioritized using Toxic Release Stream Index (TRSI) as the second tier. Afterwards, the inherent safety level of the selected streams can be determined using toxic release inherent risk assessment (TRIRA) as the third tier. The acceptability level of the inherent risk for the selected streams can be obtained using a two-region risk matrix concept. If the inherent risk level is not acceptable, the improvement of the design can be done using the inherent safety principle until the level of the inherent risk is at the tolerable or acceptable region. 3-TISQ can also be extended to evaluate the inherent safety level of fire and explosion accidents. Â© 2014 Trans Tech Publications, Switzerland.